2018
DOI: 10.4314/afrrev.v12i1.15
|View full text |Cite
|
Sign up to set email alerts
|

The causal relationship between Foreign Direct Investment (FDI) and the macro-economy of selected west African countries: Panel ARDL/Granger Causality Analysis

Abstract: This study examined the long run and short run dynamic relationships between macroeconomic variables and FDI in West Africa using recent econometric techniques for Granger non-causality and PMG/ARDL for period of 1990 to 2016. Controlling for the influence of trade openness and exchange rate, the long-run effect of Foreign Direct Investment (FDI) on economic growth and gds are found to be positive and statistically significant. FDI is found to be negative and statistically significant on unemployment indicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…However, the positive relationship that is founded between AID and economic growth is in line with the prior studies of Alemu and Lee (2015), Dalgaard et al (2004), Jena and Sethi (2019), Karras (2006), Ndambendia and Njoupouognigni (2010), Sethi et al (2019), Sothan (2018), and Tait et al (2015), but contrary to Mallik (2008), Liew et al (2012), Niyonkuru (2016), and Yiew and Lau (2018), who found a negative impact of AID on growth in recipient countries. Besides, the positive nexus between FDI and economic growth is similar to previous empirical studies of Borensztein et al (1998), Emmanuel (2014), Olawumi and Olufemi (2016), Umoh et al (2012), Onuoha et al (2018), and Zekarias (2016), suggesting that FDI is an important vehicle for the transfer of technology, which contributes to technological progress and creates a spillover effect, and thereby raises the long‐term growth rate. Indeed, FDI can bring in foreign capital and promote economic growth in developing countries.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, the positive relationship that is founded between AID and economic growth is in line with the prior studies of Alemu and Lee (2015), Dalgaard et al (2004), Jena and Sethi (2019), Karras (2006), Ndambendia and Njoupouognigni (2010), Sethi et al (2019), Sothan (2018), and Tait et al (2015), but contrary to Mallik (2008), Liew et al (2012), Niyonkuru (2016), and Yiew and Lau (2018), who found a negative impact of AID on growth in recipient countries. Besides, the positive nexus between FDI and economic growth is similar to previous empirical studies of Borensztein et al (1998), Emmanuel (2014), Olawumi and Olufemi (2016), Umoh et al (2012), Onuoha et al (2018), and Zekarias (2016), suggesting that FDI is an important vehicle for the transfer of technology, which contributes to technological progress and creates a spillover effect, and thereby raises the long‐term growth rate. Indeed, FDI can bring in foreign capital and promote economic growth in developing countries.…”
Section: Resultssupporting
confidence: 89%
“…They found that FDI has a direct positive effect on economic growth and suggested that the effect of FDI on growth is dependent on the level of democracy in the host countries. Onuoha et al (2018) explored the causal relationship between economic growth and its macroeconomic determinants in West African countries over the period 1990–2016. Their results highlighted a significant contribution of FDI to economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to apply appropriate unit root and cointegration tests in panel data, there is need to confirm the presence or absence of cross-sectional dependence in the variables (Mallick, Mallesh, & Behara, 2016;Onuoha, Okonkwo, Okoro, & Okere, 2018). To ensure the validity of the results, the following four CSD tests were applied: Breusch-Pagan LM, Pesaran scaled LM, bias-corrected scaled LM and Pesaran CD.…”
Section: Methodsmentioning
confidence: 99%
“…The current study made use of three alternative approaches (for comparison purposes), namely, mean group (MG), pooled mean group (PMG) and dynamic fixed effects (DFE) estimators. The three estimators use the maximum likelihood approach and consider the long-run equilibrium and the heterogeneity of the dynamic adjustment process (Onuoha et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation